North Namibia margin : regional tectonic evolution based on integrated analysis of seismic reflection and potential field data and modelling - Sakariassen, Rune (2007)
Rifting of the Paleozoic Gondwana supercontinent during Mesozoic time ended eventually with the breakup of Africa and South America, leading to passive margin formation and to the creation of the South Atlantic Ocean (e.g. Karner & Driscoll, 1999; Mohriak et al., 2002). Rifting began in the south and propagated towards the north, accompanied by lithosphere stretching that finally culminated in breakup and the onset of sea floor spreading. Plate motion reconstruction in the South Atlantic is controversial due to a magnetic quiet zone lasting from early Aptian to Campanian times. End of rifting and onset of seafloor spreading is by many studies estimated to range from 137 to 130 Ma in the southern part of the South Atlantic (Austin & Uchupi, 1982; Nürnberg & Müller, 1991; Gladczenko et al., 1997; Mohriak et al., 2002). The oldest magnetic seafloor-spreading anomalies recognized off Namibia are 130 Ma, and breakup is therefore considered to have occurred there in Early Cretaceous time (Rabinowitz and LaBrecque, 1979). The South Atlantic rift system created two different passive margin settings offshore Namibia, namely non-volcanic and volcanic, situated north and south of the bathymetric feature Walvis Ridge offshore North Namibia (Fig. 1.1) (Gladczenko et al., 1999). On the conjugate South America margin, the Rio Grande Rise (Fig. 1.1) represents the conjugate prominent bathymetric feature, which is related to the Tristan hot-spot plume trail (e.g. Storey, 1995; Eldholm et al., 2000; Thompson et al., 2001). North of Walvis Ridge the margin shows more similarities with the Angola margin, but without the prominent salt structures (e.g. Marton et al., 2000; Nurullina, 2006). This part has got no/little evidence of extrusive magmatic material and underplating compared to the margin south of the Walvis Ridge, which exhibits large volumes of extrusive material both offshore and onshore, and evidence of underplating (e.g. Gladczenko et al., 1997; Gladczenko et al., 1999). As petroleum exploration advances ...